HUMAN RESOURCES MANAGEMENT DEVELOPMENT OF TEACHER MOTIVATION IN MTSS CIPAR-PARE KEC. SULTAN DAULAT KOTA SUBULUSSALAM - Abdillah, Abdillah; Pohan, Annisa Addina; Anggaisa, Wensi (Universitas Dharmawangsa, 2020)
This study aims to explain the Development of Human Resources Through Work Motivation in Special Education Institutions in MTss Cipar-pare Kec. Sultan Daulat Subulussalam City can be understood in series, namely HR Development through Work Motivation. HR Development at MTss Cipar-pare Kec. Sultan Daulat Subulussalam City understood the process of improving quality through two forms, namely the performance improvement meant by the teachers, the more mature the skills and knowledge with their respective fields. And the development of human resources can affect the motivation of teacher work